Special men: The gendered militarization of the Canadian Armed Forces. (December 2017) - Lane, Andrea
The militarization of Canadian society since 9/11 has attracted considerable academic attention. What has largely escaped notice is the simultaneous process of remilitarization undergone by the Canadian Armed Forces, in which a more aggressive "warrior" posture has encouraged the development of male-only special forces units, further exacerbating the existing gendered combat/noncombat binary. This article explores this process, arguing that the state of exception created by the Global War on Terror has allowed the de facto exclusion of women from the Canadian Armed Forces' most highly valued roles, even as the military continues to assert its gender neutrality and progressive, integrated force structure.